Des lémuriens et des hommes : mythes, représentations et pratiques à Madagascar - Claire Harpet (Revue de Primatologie)
Myths and related practices reflect the richness of relationships that people have had since the beginning with lemurs, animals endemic to the island of Madagascar. Depending on the species and the ethnic group involved, the representations of lemurs differ throughout the territory: founder ancestors, benefactors, taboo, sacred, feared or evil omen, lemurs occupy many status in the heart of Madagascan bestiary.  Some traditionsare underminingtheir existence;others on the contrarycontribute totheir preservation.Thepresent article proposesreading anthropological relationshipsof men andlemursin Madagascar tothe test of timeand theglobalizing world.